A autonomia da vontade e seus efeitos jurídicos nos contratos de consumo - Almeida, Jesus Cláudio Pereira de (2018)
To analyze the principle of autonomy of the will and its legal consequences in consumer contracts, whose main objective of this thesis is to understand the role played by the supplier and how the consumer has access to the information of the contract of adhesion, to realize the without taking so many risks, as it happens in contracting by electronic means. In order to achieve this objective, we believe it is necessary to walk the path of the basic reference that collaborates to build the thesis itself and that defines its specific objectives, namely: (i) to know the institute of contracts and its discipline in consumer law , as well as in civil law as a link to understand the contractual consumerist system; (ii) evidence of the principles and fundamentals that support consumer protection, as a vulnerable and hyposufficient part of consumer relations; (iii) define the peculiarities of the contracts, as well as the reporting principles; (iv) identify the legal and administrative aspects of the contracts, observing the limits of the proposed theme; (v) to study the context in which the consumer relations deriving from contracts in compliance with the CDC rules are inserted; and (vi) verify and discuss the application of the principle of autonomy of the will, given the consumer's access to information in the light of the Federal Constitution of 1988 and the legal consumer law, without distancing itself from the casuistry that, when submitted to the Judiciary, has the function of balancing the primitive relation detrimental. In order to deal with this task, the exploratory research of a deductive investigative approach and the bibliographic research technique, with a theoretical reference based on secondary sources, especially the specialized doctrine and jurisprudence, were used as methodological support. As for the organization, the work is divided into five chapters considered essential to surround the theme then proposed. Thus, in the first chapter, we discuss the conception of the contract as a norm and its historical evolution. The second chapter is dedicated to the study of principiology that gives support to consumer relations, from the Federal Constitution, spreading to the Consumer Code, as well as civil procedural law. Then, in the third chapter, the study aims to understand the assumptions, requirements and formation of consumption contracts, ending with the contract of adhesion and the general contractual clauses. The fourth chapter is dedicated to the study of the autonomy of the will, as well as the necessary principles that help and justify the hermeneutics of the institute. The fifth and last chapter explores, within the scope of the research, the legal reflexions of the autonomy of the will in the consumer contracts, considering the crisis and the new social reality of the contract, especially the contracts realized by electronic means, as well as the new expectations created by consumers, on account of the right to have access to information about the product or service, ending with the possibility of intervention by the State Judge as one of the limiters of contractual freedoms, when this relationship is unbalanced. From the study, it is noted that, despite the uncertainty in jurisprudence specifically regarding the right of consumers to have access to information, we argue that this principle is the minimum security that consumers need to have before they think about buying a product or hire a service